Platelet Control of Fibrin Distribution and Microelasticity in Thrombus Formation Under Flow. Issue 4 (April 2016) - Swieringa, Frauke; Baaten, Constance C.F.M.J.; Verdoold, Remco; Mastenbroek, Tom G.; Rijnveld, Niek; van der Laan, Koen O.; Breel, Ernst J.; Collins, Peter W.; Lancé, Marcus D.; Henskens, Yvonne M.C.; Cosemans, Judith M.E.M.; Heemskerk, Johan W.M.; et al.
Abstract : Objective—: Platelet- and fibrin-dependent thrombus formation is regulated by blood flow and exposure of collagen and tissue factor. However, interactions between these blood-borne and vascular components are not well understood. Approach and Results—: Here, we developed a method to assess whole-blood thrombus formation on microspots with defined amounts of collagen and tissue factor, allowing determination of the mechanical properties and intrathrombus composition. Confining the collagen content resulted in diminished platelet deposition and fibrin formation at high shear flow conditions, but this effect was compensated by a larger thrombus size and increased accumulation of fibrin in the luminal regions of the thrombi at the expense of the base regions. These thrombi were more dependent on tissue factor–triggered thrombin generation. Microforce nanoindentation analysis revealed a significantly increased microelasticity of thrombi with luminal-oriented fibrin. At a low shear rate, fibrin fibers tended to luminally cover the thrombi, again resulting in a higher microelasticity. Studies with blood from patients with distinct hemostatic insufficiencies indicated an impairment in the formation of a platelet–fibrin thrombus in the cases of dilutional coagulopathy, thrombocytopenia, Scott syndrome, and hemophilia B. Conclusions—: Taken together, our data indicate that (1) thrombin increases the platelet thrombus volume; (2) tissue factor drives the formation of fibrin outside of the platelet thrombus; (3) limitation of platelet adhesion redirects fibrin from bottom to top of the thrombus; (4) a lower shear rate promotes thrombus coverage with fibrin; (5) the fibrin distribution pattern determines thrombus microelasticity; and (6) the thrombus-forming process is reduced in patients with diverse hemostatic defects. Abstract : Supplemental Digital Content is available in the text.